REFLECTION AS A QUALITY FOR EFFECTIVE PROFESSIONAL ACTIVITIES AND SELF-DEVELOPMENT - K.O. Kaziyev; Sh.N.Bisenova; F. SH. Khamidullayev (QO‘QON UNIVERSITETI XABARNOMASI, 2022)
Modern innovative learning technologies are guided by the reflexive processes of the subject. In the process of professional training, a person is formed as a professional, which becomes possible only taking into account personal factors that subsequently determine the development of professional reflection. Reflection is defined as a necessary component of the cognitive procedure and an important characteristic of the individual. The development of reflection in future psychologists is one of the urgent problems in the modern educational process. This article presents an analysis of the results of a stating experiment on the development of reflection in future psychologists to identify their abilities for analysis and introspection, professional and personal self-development. In order to achieve the goals of the desired problem, we have identified applicable methods that allow us to determine the levels of development of reflection in future psychologists by components. The methods presented in the article allow us to further develop an educational and methodological complex for the development of reflection in future psychologists.